Assessment of the Nutritional Qualities of a Locally-Produced Weaning Blend of Sorghum Ogi Flour Fortified with Bambara Groundnut Flour - Stella M, Adeyemo; Olufemi G, Abimbola (The International Journal of Biotechnology, 2019)
This study investigated the nutritional quality of a locally-produced weaning blend of sorghum ogi flour fortified with Bambara groundnut (BGN) flours and the role of lactic acid bacteria (LAB) as starter in the reduction of anti-nutrients in the pre-treated BGN flours. LAB were isolated from fermented sorghum ogi, processed into flour. BGN were processed into flours using three pre-treatment methods and used to fortify the sorghum ogi flour in ratio 60:40. Proximate composition and the breakdown of anti-nutritional factors by LAB were monitored in the pre-treated BGN flours using standard procedures. Sensory, organoleptic attributes and shelf-life of the weaning blends were determined. Sorghum ogi flour fortified with roasted BGN flour had improved nutritional value; protein, ether extract, ascorbic acid, riboflavin, β-carotene, calcium, and phosphate (mg/100g) 20.16, 6.43, 21.00, 0.13, 90.00, 145.00 and 280.00 respectively compared to boiled and soaked BGN flours. There was a reduction in the anti-nutritional factors of the pre-treated BGN flours when fermented with selected starter. Tannin, phytate, protease and trypsin inhibitors reduced significantly (p< 0.05) from 0.074 - 0.048; 5.901- 5.001; 0.052 - 0.043 and 0.137 -0.110 respectively. The shelf-life monitoring and organoleptic assessment showed that sorghum Ogi flour fortified with roasted BGN flour had a prolonged shelf life and was generally accepted when compared to other weaning blends. The study concluded that the weaning blend had improved nutritional composition required for a growing infant. LAB could be used as starters to reduce anti-nutritional factors and extend the shelf-life of pre-treated Bambara groundnut-sorghum ogi blends.